SISTEM PENDUKUNG KEPUTUSAN KENAIKAN PANGKAT KARYAWAN DENGAN METODE TOPSIS PADA PT. TRI SAUDARA SENTOSA INDUSTRI - Elkin Rilvani; Ma'ruf Setiadi2 (Jurnal SIGMA, 2019)
Employees are one of the most important assets owned by the company in its efforts to maintain survival, develop, the ability to compete and make a profit. To improve employee performance at PT. Tri Saudara Sentosa Industri, there needs to be a promotion for employees. However, the current appointment process for employees is not precise, because the calculations made are not yet detailed, apart from that there is still the potential for subjectivity that causes jealousy among employees. Decision support system (SPK) can be defined as a system intended to support managerial decision makers in an unstructured decision situation. The TOPSIS (Technique For Others Preference by Similarity to Ideal Solution) method uses the concept that the best alternative not only has the shortest distance from the positive ideal solution, but also has the longest distance from the negative ideal solution. From the calculation of determining employee promotions using the TOPSIS method, the highest calculation results will then be determined as recipients of employee promotions. Decision Support System (SPK) with the TOPSIS method is able to facilitate the determination of employee promotions with more accurate calculations Keywords: Employees, Decision Support Systems, TOPSIS (Technique For Others Preference by Similarity to Ideal Solution)